The Implementation of Domestic Violence Act in India: A State-Level Analysis - Anamika, Das; Lakshmana, C.M. (Bangalore, 2020)
To protect women against discrimination, the law empowers women through various ways by equipping them with right and power to enable them to fight against the patriarchal nature of society. The main purpose of this paper is to probe into the provisions made under the Protection of Women from the Domestic Violence Act, 2005 (PWDVA, 2005) and to explain the roles and responsibilities of different authorities under this Act. This paper analyses secondary data to find the reasons for the failure of the PWDVA which includes highly uneven state-wise budgetary allocations, delays in passing orders, lack of clear directions to stakeholders about their roles and responsibilities for effective implementation. There is an urgent need to strengthen the PWDV Act for the victims to get fruitful justice on time.
Keywords: Domestic Violence; India